Guillain Barre Syndrome pada Kehamilan - Hermin Sabaruddin; Pribakti Budinurdjaja; Fakhrurrazy Fakhrurrazy (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Guillain-Barre Syndrome (GBS) is a clinical syndrome characterized by the presence of the complete flaksid that occurs in acute. GBS associated with autoimmune reaction that affect peripheral nerve, radix, and cranial nerve. The incidence of GBS is 1 – 2 per 100,000 people/year. The incident was followed by increased age and the increasing population of obstetrics. GBS in pregnancy ranged from 13% in the first trimester, 47% in the second trimester, and 40% in the third trimester. In this case report reported Mrs. M 27 years old with a diagnosis of G2P1A0 h. 39-40 weeks + insimanation + living single fetal Presentation Head + Inpartu kala II + GBS + Failed + Vacuum Severily Underweight (BMI = 17) + TBJ 3000 Gr. Diagnosis of GBS are enforced based on anamnesis, physical examination and complementary examinations. From a previous illness history found anamnesis the weakness of limbs beginning in 2016. A history of the use of breathing apparatus and admitted tot the ICU in the first pregnancy. Mrs. M had a history of infections before being diagnosed with GBS. On this second pregnancy patients cannot move lower extremity but upper extermity is still functioning. Physical examination result of mothers and babies in the normal range even though found in conditions of severily BMI underweight. The patient finally decided to SC (section caesaria) and applied the IUD intracaesarean GBS in pregnancy is a coincidental. GBS is rarely aggravate pregnancy, but if not quickly identified and handled can enhance the high morbidity in both mother and fetus. In acute attacks (AIDP) in pregnant women with GBS increase stress on the mother or the fetus. The stress that occurs can also stimulate the immune system to produce prostaglandins, resulting in premature birth. Patients can give birth when the gestational age is still 7 months. It was different in the second pregnancy in this case where the patient was diagnosed with chronic inflammatory demyelinating polyradiculopathy (CIDP) so that GBS did not affect the mother and the fetus.